Using Mentimeter in Action Research to Enhance Students' Engagement in Online Learning - Ima Chusnul Chotimah; Dian Anik Cahyani; Maskurin Fajarina; Abdullah Farih (JEELL (Journal of English Education, Linguistics and Literature), 2025)
In online learning, improving student participation in EFL classes is still a growing concern. Fortunately, several studies have demonstrated a favorable relationship between using technology to increase student engagement. This action research study investigated the effect of using a mentimeter on the student’s engagement in online learning. The study used a classroom cyclic action-research approach to enhance student engagement over a month. The participants were 22 second-year-undergraduate students from the local university in Indonesia, consisting of 7 males and 15 females. Findings revealed that engaging students in engaged discussion enhances their engagement and achievement in the word cloud and open-ended questions model using a mentimeter. The students gave positive responses after being taught by using a mentimeter. The findings support the enhancement of the students’ engagement in English as a Foreign Language (EFL) learning context and suggest useful implications for educators.